1998
DOI: 10.1042/bj3340695
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of metallothionein isoforms (MT-1 and MT-2) in the rat testis

Abstract: It has been a long-lasting controversial issue as to whether or not the male genital organs, such as the testis and prostate, contain metallothioneins (MTs), a group of cysteine-rich heavy-metal-binding proteins that play a role in detoxifying heavy metals such as cadmium (Cd). Earlier studies reported that the rodent testis lacks MTs and concluded that this is why the testis is very susceptible to Cd, although other indirect experimental evidence suggests that MTs are present in this organ. A deficiency of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
(30 reference statements)
3
26
0
1
Order By: Relevance
“…These data are in accordance with data published by Suzuki et al [37]. The long-standing debate about whether MT is expressed in testicular tissue thus seems to be resolved.…”
Section: Role Of Mt In Modifying CD Effects In Reproductive Tissuessupporting
confidence: 82%
“…These data are in accordance with data published by Suzuki et al [37]. The long-standing debate about whether MT is expressed in testicular tissue thus seems to be resolved.…”
Section: Role Of Mt In Modifying CD Effects In Reproductive Tissuessupporting
confidence: 82%
“…In the testis, a blood-testicular barrier has been formed as a defense mechanism against the approach of various xenobiotic substances. Moreover, oxidative-stress responsive proteins HO-1 and MT-1/2 also express in rat testes (Ozawa et al, 2002;Suzuki et al, 1998). Roles of HO-1 and MT-1/2 in the testes remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MT-1/2 was found to express highly in control rat testes, and was not induced by MMS administration. Earlier studies have reported that the rodent testis lacks MT-1/2 (Whanger et al, 1980), indicating that this lack of MT-1/2 is the reason why the testes are very susceptible to Cd, although other experimental evidence suggested that there were mRNAs which hybridized with mouse MT-1 cDNA in rat testes under physiological conditions (Wahba et al, 1994;Suzuki et al, 1998). More recently, evidence has appeared that MT-1/2 exists in rat testes by employing RT-PCR with MT-1 and MT-2 specific primers, and there are also MT-1 and MT-2 proteins (Suzuki et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 186b RNA sense and antisense probes for the MT-III from a pPCR-MMT3S plasmid, containing the MT-III coding and noncoding sequences 2021-2206 of the MT-III DNA, were labeled with digoxigenin-UTP (Boehringer Mannheim Biochemica, Germany) (Suzuki et al, 1998). The paraffin sections (5 碌m) were mounted on 3 -aminopropyltriethoxysilane-coated slides, dried at 60…”
Section: In Situ Hybridization For Demonstration Of the Mt-iii Mrnamentioning
confidence: 99%